Modulation of in vitro monocyte cytokine responses to Leishmania donovani. Interferon-gamma prevents parasite-induced inhibition of interleukin 1 production and primes monocytes to respond to Leishmania by producing both tumor necrosis factor-alpha and interleukin 1. - Reiner, N E; Ng, W; Wilson, C B; McMaster, W R; Burchett, S K (The Journal of Clinical Investigation, 1990)
Cytokines produced by mononuclear cells are important regulatory and effector molecules and evidence has been presented to support a role at least for tumor necrosis factor-alpha (TNF-alpha) and interferon-gamma (IFN-gamma) in host defense against Leishmania. In the present study, we examined the production of TNF-alpha and interleukin 1 (IL-1) by resting and IFN-gamma-primed peripheral blood monocytes infected in vitro with Leishmania donovani. Monocytes produced neither IL-1 nor TNF-alpha during challenge with Leishmania. Cells preinfected with Leishmania synthesized normal amounts of TNF-alpha, but had diminished production of IL-1 in response to stimulation with either S. aureus or lipopolysaccharide (LPS). The induction by S. aureus or LPS of IL-1 beta mRNA accumulation in infected cells was normal despite diminished intracellular or supernatant IL-1 protein and bioactivity. Thus, inhibition of IL-1 production by Leishmania most probably reflected diminished translation of IL-1 beta mRNA. Pretreatment of cells with IFN-gamma abrogated infection-induced inhibition of IL-1 production and primed cells for the production of both IL-1 and TNF-alpha upon subsequent exposure to Leishmania. These results indicate that L. donovani has evolved the capacity to infect mononuclear phagocytes, without stimulating the production of two potentially host-protective monokines. The ability of IFN-gamma to prime monocytes to produce TNF-alpha and IL-1 in response to infection with Leishmania and to prevent inhibition of IL-1 production may have implications for immunotherapy with this lymphokine. Images